Method for preparing polyacrylonitrile pre-oxidized fiber in segmented microwave mode
By combining segmented microwave treatment with hydroxyethyl acrylate pretreatment, the problems of high energy consumption and uneven heating in the pre-oxidation process of polyacrylonitrile fibers were solved, achieving a highly efficient and uniform pre-oxidation effect and improving the strength and flame retardant properties of the fibers.
Patent Information
- Application Number
- CN202511089036.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-10-24
AI Technical Summary
Existing polyacrylonitrile fiber pre-oxidation processes suffer from problems such as high energy consumption, differences in pre-oxidation effects between the inside and outside leading to low strength, poor flame retardancy, and easy slagging.
A segmented microwave processing method is adopted, which involves setting up multiple microwave generators in the microwave processing device, using microwaves of different frequencies arranged alternately, and combining them with hydroxyethyl acrylate solution pretreatment. The microwave power and fiber moisture content are controlled in segments to achieve uniform heating and oxidation inside the fiber.
It improves pre-oxidation efficiency, ensures uniform heating inside and outside the fiber, avoids strength damage and flaking caused by local over-oxidation, and enhances the fiber's breaking strength and flame retardant properties.
Smart Images

Figure CN120830168A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to a method for preparing polyacrylonitrile pre-oxidized fibers in a segmented microwave mode, and belongs to the technical field of carbon filaments prepared from polyacrylonitrile. BACKGROUND
[0002] In recent years, the flame-retardant textile market has shown a steady growth trend, and the market is still expanding. The production capacity of various flame-retardant fibers in China cannot meet the market demand. With the continuous increase of human safety awareness and the continuous improvement of flame-retardant regulations, the development of flame-retardant textiles will continue to increase, and permanent flame-retardant textiles will become a new market hotspot.
[0003] Polyacrylonitrile pre-oxidized fibers are high-performance flame-retardant fibers with heat-resistant ladder structures formed after polyacrylonitrile fibers are oxidized. The conventional pre-oxidation method mainly places PAN raw yarns in an electric heating furnace for pre-oxidation. Heat is from a heating source, and then heat convection, heat conduction and heat radiation are used to transfer heat from the outside of the PAN raw yarns to the inside. As the temperature rises, the surface layer of the PAN raw yarns is first pre-oxidized, and the ladder structure is formed preferentially, and then a dense network structure is formed. This forming method hinders the further diffusion of oxygen to the core, and as the heating time increases, the skin-core structure of the PAN raw yarns becomes more and more obvious, making it difficult to obtain high-performance carbon fibers.
[0004] Microwave heating is a heating method that uses a material to absorb microwave energy, causing the material to heat up both internally and externally. Compared to traditional heating methods, microwave heating offers advantages such as energy efficiency, ease of control, selective heating, rapid heating speed, and high efficiency. Researchers at home and abroad have attempted to apply microwaves to the pre-oxidation of PAN. However, polyacrylonitrile precursor fibers themselves do not absorb microwaves, and improving their absorption performance requires coating their surfaces with absorbing materials (such as carbon black, carbon nanotubes, and graphene). For example, CN120061016A performs microwave pre-oxidation on composite precursor fibers of cyano-carbon nanotube / acrylonitrile copolymers, utilizing the composite carbon nanotubes for absorption to improve pre-oxidation efficiency, but ignoring the important role of rapid microwave transmission and uniform distribution within the fibers. CN111691012A performs microwave oxidation on polyacrylonitrile precursor fibers impregnated with an adhesive solution, reducing processing costs by using power supply. CN118498009A performs temperature-increasing, segmented microwave treatment on polyacrylonitrile fiber mats coated with a microwave sensitizer. However, most fibers are solid structures. Although the above-mentioned method of coating with absorbing materials solves the heating consistency of the fiber core and the fiber surface, it is difficult to achieve uniform treatment effect across the entire cross-section. Some researchers use external forces to counteract skin-core formation. For example, CN107858829A microwave-oxidizes PAN fibers impregnated with adhesive / absorbing carbon materials under tension and introduces oxygen-containing gas to improve efficiency. However, after the amount of gas adsorbed into the fiber reaches saturation, it will not continue to increase with the increase in the amount of gas in the environment. Therefore, the effect of the introduced oxygen-containing gas on the oxidation rate of the fiber surface is stronger than the effect on the oxidation rate inside the fiber, and there is a risk of a skin-core structure. Summary of the Invention
[0005] In view of this, the present application provides a method for preparing polyacrylonitrile pre-oxidized fibers by segmented microwaves, which not only effectively solves the problem of high energy consumption in the pre-oxidation of polyacrylonitrile fibers, but also effectively eliminates the problems of low strength, poor flame retardancy, and easy falling off caused by the difference in pre-oxidation effects inside and outside the fibers.
[0006] Specifically, this application is implemented through the following solutions:
[0007] A method for preparing polyacrylonitrile pre-oxidized fibers using a segmented microwave method, comprising the following steps:
[0008] Step 1: immerse the polyacrylonitrile fiber in a hydroxyethyl acrylate solution for pretreatment, take it out, and dry it.
[0009] Step two, the pretreated polyacrylonitrile fiber is placed in a microwave treatment device provided with a plurality of microwave generators, and the polyacrylonitrile fiber is subjected to segmented pre-oxidation: first segment pre-oxidation: 600-800W for 5-10min, second segment pre-oxidation: 1000-1200W for 10-20min, and third segment pre-oxidation: 1500-2000W for 20-30min.
[0010] The above scheme uses a hydroxyethyl acrylate solution to pretreat the polyacrylonitrile fiber, and a polar small-molecular-weight substance with good water solubility penetrates into the polyacrylonitrile fiber. In the segmented microwave treatment, the polar small-molecular-weight substance in the polyacrylonitrile fiber interacts with the microwave field, effectively increasing the dielectric constant and loss factor, enhancing the microwave absorption effect, and improving the pretreatment uniformity. In the segmented microwave process, the first segment pre-oxidation is performed at a lower power to promote uniform heating of the fiber and initiate cyclization reaction and form a stable structure prototype. The second segment pre-oxidation is performed at a medium power to cause oxidation reaction and introduce oxygen-containing groups, thereby improving thermal stability. The third segment pre-oxidation is performed at a high power to release oxygen elements from the hydroxyethyl acrylate, intensify the oxidation reaction, and complete the structure stabilization.
[0011] Further, as preferred:
[0012] In step one,
[0013] The pretreatment temperature is 60-70℃, and the time length is 10-30min. More preferably, the pretreatment temperature is 65℃.
[0014] The drying temperature is 70-80℃. Preferably, the drying temperature is 80℃.
[0015] The concentration of the hydroxy acrylate solution is 5-15g / L. More preferably, the concentration of the hydroxy acrylate solution is 10g / L.
[0016] In this step, hydroxyethyl acrylate is a small-molecular-weight substance with good water solubility, which can penetrate into the polyacrylonitrile fiber during pretreatment and form a uniform distribution in the fiber. In the microwave pre-oxidation process, the polar molecules of hydroxyethyl acrylate are more likely to interact with the microwave electric field, increasing the dielectric constant and loss factor, so that more microwave energy is converted into heat energy, thereby enhancing the microwave absorption effect. The uniformly distributed hydroxyethyl acrylate not only improves the pre-oxidation efficiency, but also improves the pretreatment uniformity, avoiding problems such as strength damage and ash and slag dropping caused by local excessive oxidation.
[0017] The carboxylate group in hydroxyethyl acrylate is decomposed into carboxyl group at high temperature, which can promote the pre-oxidation reaction inside the fiber, especially the cyclization reaction. The hydroxyethyl acrylate contains a large amount of oxygen, which can release oxygen elements at high temperature to promote the oxidation reaction.
[0018] In step two,
[0019] The microwave pre-oxidation treatment device is provided with eight microwave generators arranged in two layers. The microwave generators with a frequency of 915MHz and the microwave generators with a frequency of 2.45GHz are alternately arranged in each layer, and the microwave generators with a frequency of 915MHz and the microwave generators with a frequency of 2.45GHz are staggered in the upper and lower layers. Different frequencies of microwaves have different penetration depths, high frequency penetrates shallowly, and low frequency penetrates deeply. Simultaneous use of high frequency and low frequency can cover different depth layers, thereby realizing more uniform heating.
[0020] The first pre-oxidation is 600W for 10min, the second pre-oxidation is 1000W for 10min, and the third pre-oxidation is 2000W for 20min.
[0021] Before being placed in the microwave treatment device, the polyacrylonitrile fiber is also subjected to a humidification treatment, and the moisture content of the polyacrylonitrile fiber is controlled at 5-15%, and preferably 12%. Water is a typical wave-absorbing material, and the presence of a small amount of water can improve the pre-oxidation efficiency and reduce energy consumption in cooperation with the hydroxyethyl acrylate.
[0022] In the segmented microwave treatment of this process, the higher the microwave power, the faster the heating speed. Under the condition of low power (600-800W) for 5-10min, the fiber can be uniformly heated and the cyclization reaction can be initiated to form a stable structure prototype. Then, under the condition of medium power (1000-1200W) for 10-20min, the oxidation reaction is started, oxygen-containing groups are introduced, and the thermal stability is improved. Finally, under the condition of high power (1500-2000W) for 20-30min, the hydroxyethyl acrylate releases oxygen elements, the oxidation reaction is intensified, and the structure is stabilized. BRIEF DESCRIPTION OF DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiments or prior art description. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creating any creative labor.
[0024] Figure 1 The structure of the microwave treatment device in the present application is shown in the following figure,
[0025] Reference numerals in the figure: 1. first microwave generator, 2. second microwave generator, 3. third microwave generator, 4. fourth microwave generator, 5. fifth microwave generator, 6. sixth microwave generator, 7. seventh microwave generator, 8. eighth microwave generator, 9. body;
[0026] Figure 2 This is the SEM image of the polyacrylonitrile pre-oxidized fiber prepared in Example 1. DETAILED DESCRIPTION
[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application more clearly understood, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of this application.
[0028] In this embodiment, the standards and methods used for detection are as follows:
[0029] 1) The tensile breaking strength and its coefficient of variation of polyacrylonitrile fiber are tested in accordance with the national standard GB / T 14337-2022 "Test method for tensile properties of chemical staple fibers". Specifically, a YG 006 electronic single fiber strength tester is used for testing, with a gauge of 20 mm, a tensile speed of 10 mm / min, and 50 tests per sample to obtain the average value. The coefficient of variation of breaking strength refers to the degree of difference between the breaking strengths of multiple specimens under the same conditions. It is usually expressed as the standard deviation divided by the mean, and its value ranges from 0 to 1. When the coefficient of variation is close to 0, it means that the breaking strength of the specimen is relatively concentrated and the variability is small; when the coefficient of variation is close to 1, it means that the breaking strength of the specimen is widely distributed and the variability is large.
[0030] 2) The limiting oxygen index is determined in accordance with the national standard GB / T 5454-1997 "Textile combustion performance test oxygen index method", and each sample is tested three times and the average value is taken.
[0031] All reagents used were commercially available unless otherwise specified.
[0032] Example 1
[0033] This embodiment provides a method for preparing polyacrylonitrile pre-oxidized fibers using a segmented microwave method. The embodiment of this application is described below in conjunction with the accompanying drawings.
[0034] Step 1: Pretreatment: Immerse the polyacrylonitrile fiber in a 10 g / L aqueous solution of hydroxyethyl acrylate at 65° C., take it out after 25 minutes, dehydrate it, and dry it at 80° C. until the moisture content is 12%.
[0035] Step two, pre-oxidation: the fiber with 12% moisture content was transferred into the microwave processing device along the arrow direction for segmented microwave pre-oxidation treatment. First segment: 600W for 10min, second segment: 1000W for 10min, third segment: 2000W for 20min.
[0036] In this process, the structure of the microwave processing device is as shown in Figure 1 The microwave processing device includes a body 9, and distributed in the body 9: a first microwave generator 1, a second microwave generator 2, a third microwave generator 3, a fourth microwave generator 4, a fifth microwave generator 5, a sixth microwave generator 6, a seventh microwave generator 7, and an eighth microwave generator 8. The frequencies of the first microwave generator 1, the fourth microwave generator 4, the sixth microwave generator 6, and the seventh microwave generator 7 are 915MHz, and the frequencies of the second microwave generator 2, the third microwave generator 3, the fifth microwave generator 5, and the eighth microwave generator 8 are 2.45GHz.
[0037] The pre-oxidized polyacrylonitrile fiber of Example 1 was observed by electron microscopy to observe the pre-oxidation effect, and the results are shown in Table 2: although there are shallow grooves and a small amount of solid particle deposition on the surface of the fiber after pre-oxidation treatment, there is no obvious powder residue adhesion, and the fiber does not have the problem of residue falling.
[0038] Comparative Example 1
[0039] This example is the same as Example 1, except that no pretreatment is performed.
[0040] Table 1: Effect of pretreatment
[0041]
[0042] As can be seen from Table 1: compared with the pre-oxidized fiber of Comparative Example 1, the pre-oxidized fiber of Example 1 has higher breaking strength, larger limiting oxygen index, and smaller coefficient of variation of breaking strength. This is because the polar molecules of hydroxyethyl acrylate are more easily interacted with the microwave electric field, increasing the dielectric constant and loss factor, so that more microwave energy is converted into heat energy, thereby enhancing the microwave absorption effect. The uniform distribution of hydroxyethyl acrylate improves the uniformity of pre-oxidation, avoiding the problems of uneven strength and residue falling caused by local over-oxidation.
[0043] Example 2
[0044] This example is the same as Example 1, except that the pretreatment temperature is replaced by 55°C and 75°C respectively instead of 65°C in Example 1, and the results are shown in Table 2.
[0045] Table 2: Effect of different pretreatment temperatures
[0046] Temperature Breaking strength Coefficient of variation of breaking strength Limiting oxygen index Whether or not the phenomenon of dropping of the slag occurred 55℃ 5.47 cN / dtex 0.16 33% Slight 65℃ 5.98 cN / dtex 0.08 36% No 75℃ 5.91 cN / dtex 0.09 37% No .
[0047] As can be seen from Table 2: When the pretreatment temperature is low (55°C), the breaking strength and limiting oxygen index of the pre-oxidized fiber are both low, and the coefficient of variation of the breaking strength is large. At the same time, there is a slight phenomenon of slagging. When the temperature continues to rise after reaching 65°C, it is not conducive to improving the fiber properties, but energy consumption increases. This is because when the temperature is low, the fiber swelling degree is insufficient, and it is difficult for hydroxyethyl acrylate to penetrate into the fiber and achieve uniform distribution. The research results show that 65°C can meet the requirements.
[0048] Example 3
[0049] The configuration of this embodiment is the same as that of embodiment 1, except that the concentration of the pretreatment agent is replaced from 10 g / L to 2 g / L, 5 g / L, 8 g / L, 12 g / L, 15 g / L, and 20 g / L, respectively. The results are shown in Table 3.
[0050] Table 3: Effect of Hydroxyethyl Acrylate Concentration
[0051]
[0052]
[0053] As can be seen in Table 3, as the concentration of hydroxyethyl acrylate increases, the breaking strength shows a trend of first increasing and then decreasing, while the breaking strength coefficient of variation shows a trend of first decreasing and then increasing. Simultaneously, the limiting oxygen index increases with increasing hydroxyethyl acrylate concentration. When the hydroxyethyl acrylate concentration continues to increase beyond 10 g / L, the limiting oxygen index no longer changes significantly. However, slight slagging occurs again when the hydroxyethyl acrylate concentration reaches 20 g / L. This is because the hydroxyethyl acrylate concentration is too low to achieve uniform distribution within the fiber. When the concentration is too high, the amount of hydroxyethyl acrylate adsorbed on the fiber surface is greater than that within the fiber, resulting in uneven oxidation and even the possibility of a skin-core structure. Therefore, the pretreatment agent concentration is preferably 5 to 15 g / L, with 10 g / L being optimal.
[0054] Example 4
[0055] The configuration of this embodiment is the same as that of embodiment 1, except that in the pre-oxidation process, the moisture content of the fiber is replaced by 12% to 4%, 5%, 15% and 20%.
[0056] Table 4: Effect of fiber moisture content
[0057] Moisture content Breaking strength Coefficient of variation of breaking strength Limiting oxygen index Whether or not the phenomenon of dropping of the slag occurred 3% 4.76 cN / dtex 0.27 31% Slight 5% 5.59 cN / dtex 0.15 34% No 12% 5.98 cN / dtex 0.08 36% No 15% 5.89 cN / dtex 0.07 36% No 20% 5.66 cN / dtex 0.23 33% Slight .
[0058] As can be seen from Table 4, with the increase of water content, the breaking strength and limiting oxygen index show a trend of first increasing and then decreasing, and the coefficient of variation of breaking strength shows a trend of first decreasing and then increasing. In addition, too low (3%) or too high (20%) water content may cause slight slagging. This is because water molecules have strong polarity and can efficiently absorb microwave energy and convert it into heat energy. When the water content is low, the heating efficiency is low, and the pre-oxidation is insufficient, and when the water content is too high, the steam generated by water evaporation volatilizes rapidly from the inside to the outside of the fiber, resulting in uneven distribution of water content in the fiber, leading to uneven pre-oxidation. Therefore, the optimal value of water content in the fiber is 12%.
[0059] Comparative Example 2
[0060] This comparative example is the same as the setting of Example 1, except that only the microwave generator with a frequency of 915 MHz, i.e. the first microwave generator 1, the fourth microwave generator 4, the sixth microwave generator 6 and the seventh microwave generator 7, is turned on during pre-oxidation.
[0061] Comparative Example 3
[0062] This comparative example is the same as the setting of Example 1, except that only the microwave generator with a frequency of 2.45 GHz, i.e. the second microwave generator 2, the third microwave generator 3, the fifth microwave generator 5 and the eighth microwave generator 8, is turned on during pre-oxidation.
[0063] Comparative Example 4
[0064] This comparative example is the same as the setting of Example 1, except that no segmented pre-oxidation is performed, i.e.
[0065] Step one, pretreatment: immerse the polyacrylonitrile fiber in a 10 g / L hydroxyethyl acrylate aqueous solution at 65°C, take it out after 25 minutes, dehydrate, and dry at 80°C to a water content of 12%.
[0066] Step two, pre-oxidation: transfer the fiber with a water content of 12% into a microwave treatment device and perform microwave pre-oxidation treatment at 600W for 40 minutes.
[0067] Comparative Example 5
[0068] This comparative example is the same as the setting of Example 1, except that no segmented pre-oxidation is performed, i.e.
[0069] Step one, pretreatment: immerse the polyacrylonitrile fiber in a 10 g / L hydroxyethyl acrylate aqueous solution at 65°C, take it out after 25 minutes, dehydrate, and dry at 80°C to a water content of 12%.
[0070] Step two, pre-oxidation: the water content of 12% of the fiber into the microwave processing device, 1000W microwave pre-oxidation treatment for 40min.
[0071] Comparative Example 6
[0072] This comparative example is the same as the setting of Example 1, the difference is that no segmented pre-oxidation, namely:
[0073] Step one, pretreatment: 65℃, polyacrylonitrile fiber immersed in 10g / L hydroxyethyl acrylate aqueous solution, 25min after taking out, dehydration, 80℃ drying to water content in 12%.
[0074] Step two, pre-oxidation: the water content of 12% of the fiber into the microwave processing device, 2000W microwave pre-oxidation treatment for 40min.
[0075] Comparative Example 7
[0076] CN118498009A is used as Comparative Example 7.
[0077] Comparative Examples 1 to 7 and Example 1 are different in preparation process, energy consumption and pre-oxidation effect as follows:
[0078] Table 5: Properties of polyacrylonitrile pre-oxidized fiber prepared in Comparative Examples 2-7 and Example 1
[0079]
[0080]
[0081] As can be seen from Table 5, compared with Example 1, the breaking strength of polyacrylonitrile pre-oxidized fiber prepared by only starting the microwave generator with a frequency of 915MHz (Comparative Example 2) or only starting the microwave generator with a frequency of 2.45GHz (Comparative Example 3) is smaller, the coefficient of variation of breaking strength is larger, and the limiting oxygen index value is smaller. This is because the penetration depth of microwaves with different frequencies is different, high frequency penetrates shallowly, low frequency penetrates deeply, and the use of high frequency and low frequency can cover different depth layers, thereby achieving more uniform heating.
[0082] Table 5 data also shows that when no segmented pre-oxidation is used, the breaking strength of the pre-oxidized fiber gradually decreases with increasing power, but the limiting oxygen index value gradually increases, but when the power is too large (Comparative Example 6), a slight dropping phenomenon occurs. This is because, if the power is too low, the pre-oxidation is not sufficient, the flame retardant performance is poor, but the fiber strength is large; the pre-oxidation degree is gradually improved with increasing power, and the flame retardant performance is improved, but when the power is too large, the pre-oxidation is not uniform, and local over-oxidation occurs, resulting in a dropping phenomenon.
[0083] From the data in Example 1 and Table 5, it can be seen that the breaking strength and limiting oxygen index value of Comparative Example 7 are low, and the coefficient of variation of breaking strength is large. This is because, in Comparative Example 7, although the fibers are pre-oxidized in sections, the microwave photosensitizer is coated on the surface of the fibers, the fibers are not treated by multiple frequency microwaves at the same time, and the high concentration of oxygen introduced can cause excessive oxidation of the fiber surface to form a skin-core structure.
[0084] The above embodiments only express several possible implementation manners of the present application, and the description is relatively specific and detailed, but it should not be understood as a limitation on the patent scope of the present application. The embodiments also do not limit the protection scope in the claims of the present application. For those skilled in the art, without departing from the concept of the present application, several modifications and improvements can be made, and any equivalent implementation or change made without departing from the present application shall be included in the present application.
Claims
1. A process for the preparation of polyacrylonitrile pre-oxidized fibers in a segmented microwave mode, characterized by, The steps are as follows: Step one, polyacrylonitrile fibers are immersed in a hydroxyethyl acrylate solution for pretreatment, taken out, dried, Step two, the pretreated polyacrylonitrile fibers are placed in a microwave treatment device provided with multiple microwave generators, and the polyacrylonitrile fibers are subjected to segmented pre-oxidation: first segment pre-oxidation: 600-800W for 5-10min, second segment pre-oxidation: 1000-1200W for 10-20min, and third segment pre-oxidation: 1500-2000W for 20-30min.
2. A process for the preparation of polyacrylonitrile pre-oxidized fibers in sections by microwave, according to claim 1, characterized by the fact that: In step one, the pretreatment temperature is 60-70℃, and the time length is 10-30min.
3. A process for the preparation of polyacrylonitrile pre-oxidized fibers in sections by microwave, according to claim 1, characterized by the fact that: In step one, the pretreatment temperature is 65℃.
4. The process for the preparation of polyacrylonitrile pre-oxidized fibers in sections by microwave according to claim 1, characterized in that: In step one, the concentration of the hydroxyethyl acrylate solution is 5-15g / L.
5. The process for the preparation of polyacrylonitrile pre-oxidized fibers in sections by microwave according to claim 1, characterized in that: In step one, the drying temperature is 70-80℃.
6. A process for the preparation of polyacrylonitrile pre-oxidized fibers in sections by microwave, according to claim 1, characterized by the fact that: The microwave treatment device is provided with eight microwave generators, respectively emitting two frequencies of 915MHz and 2.45GHz.
7. A process for the preparation of polyacrylonitrile pre-oxidized fibers in sections by microwave, according to claim 6, characterized by the fact that: Along the direction of the polyacrylonitrile fibers entering the microwave treatment device, the frequencies of the four microwave generators in the front are 915MHz, and the frequencies of the four microwave generators in the back are 2.45GHz.
8. The method according to claim 1, wherein, first segment pre-oxidation: 600W for 10min, second segment pre-oxidation: 1000W for 10min, third segment pre-oxidation: 2000W for 20min.
9. The process for the preparation of polyacrylonitrile pre-oxidized fibers in sections by microwave according to any one of claims 1 to 8, characterized by the fact that: Before being placed in the microwave treatment device, the polyacrylonitrile fibers are also subjected to humidification treatment, and the water content of the polyacrylonitrile fibers is controlled to be 5-15%.
Citation Information
Patent Citations
Method for preparing polyacrylonitrile pre-oxidized yarns in microwave oxidation method
CN107858829A
Microwave pre-oxidation technology for electric-control-type polyacrylonitrile protofilament
CN111691012A
Microwave pre-oxidation method based on cyanation carbon nanotube modified polyacrylonitrile-based carbon fiber precursor
CN120061016A